PENGARUH PHYSICAL EVIDENCE TERHADAP KEPUASAN KONSUMEN (STUDI KASUS DI SURF CAFÉ KOTA BIMA) - Azwar Tryadi dan Muhajirin (JOURNAL SCIENTIFIC OF MANDALIKA (JSM), 2021)
In a modern era like today, business opportunities in the culinary world continue to grow and almost never subside, making business in this field very promising. One of the phenomena we encounter is the increasing number of culinary businesses. This study aims to see the effect of physical evidence on customer satisfaction. The research method in this research is quantitative with associative research type. Based on the results of hypothesis testing carried out in this study, it is found that physical evidence has a significant effect on customer satisfaction.